2020
DOI: 10.1016/j.envres.2019.108604
|View full text |Cite
|
Sign up to set email alerts
|

Relation between in utero arsenic exposure and growth during the first year of life in a New Hampshire pregnancy cohort

Abstract: Background-We have previously reported that in utero arsenic exposure is associated with increased length and other anthropometric outcomes at birth in a U.S. cohort. However, it is unknown whether these anthropometric differences persist through early life. Objectives-We assessed in utero arsenic exposure in relation to attained anthropometry and growth trajectories through the first year of life. Methods-Among 760 mother-infant pairs from the New Hampshire Birth Cohort Study, we assessed in utero arsenic exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…More evidence concluded that maternal and in-utero exposure to arsenic increases the risk of infections during the first year of life, particularly diarrhea and respiratory symptoms [40]. Additionally, male infants were observed to have increased length and decreased head and chest circumference, later confirmed by another study, and found to persist for the first year of life [42,43,85,97].…”
Section: Arsenic and New-born Mortalitymentioning
confidence: 94%
“…More evidence concluded that maternal and in-utero exposure to arsenic increases the risk of infections during the first year of life, particularly diarrhea and respiratory symptoms [40]. Additionally, male infants were observed to have increased length and decreased head and chest circumference, later confirmed by another study, and found to persist for the first year of life [42,43,85,97].…”
Section: Arsenic and New-born Mortalitymentioning
confidence: 94%
“…The CONTAM Panel identified 40 additional papers that were not included in the EFSA 2009 Opinion. In 25 of these papers, As exposure and birth weight were reported, but the studies were not considered further either because exposure was assessed by total As in blood, serum or urine and it was not possible to evaluate the contributions of organic vs. inorganic As (Bermúdez et al., 2015 ; Bloom et al., 2015 ; Deyssenroth et al., 2018 ; Govarts et al., 2016 ; Guan et al., 2012 ; Hameed et al., 2019 ; Henn et al., 2016 ; Lee et al., 2021 ; Liao et al., 2018 ; Liu et al., 2018 ; Mullin et al., 2019 ; Nyanza et al., 2020 , Rahman, Oken, et al., 2021 ; Remy et al., 2014 ; Röllin et al., 2017 ; Wang, Li, Zhang, et al, 2018 ; Wang, Wang, Wang, et al., 2022 ; Xu et al., 2011 ; Xu, Hansen, et al., 2022 ), and/or the papers did not explicitly report associations between As exposure and birth weight (Fei et al., 2013 ; Mullin et al., 2019 ; Muse et al., 2020 ; Remy et al., 2014 ; Saha et al., 2012 ; Thomas et al., 2015 ; Wai et al., 2020 ; Wei, Shi, et al., 2017 ).…”
Section: Assessmentmentioning
confidence: 99%
“…Four cohort studies including mother–child pairs investigated the associations between iAs and children's growth, two of which were from Bangladesh and one from the US (Gardner et al., 2013 ; Igra et al., 2021 ; Muse et al., 2020 ; Saha et al., 2012 ). One of the studies measured concentrations of iAs in urine only in mothers during pregnancy, whereas the other two measured it also in the children.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation